Saudi Arabia’s defence industrial transition: from vision to reality? - Matthews, Ron; Romainor, Hafeez Iskandar Bin; Ansari, Irfan (Taylor & Francis, 2025)
The Kingdom of Saudi Arabia has long harboured defence industrial ambitions, but with minimal practical impact. Efforts have been stymied by overly complex regulation, stuttering institutional commitment and an inchoate defence industrial strategy. Vision 2030 changed all that, driven by a 50% localisation goal by 2030. The Kingdom has the world’s 5th biggest defence budget and is its 3rd biggest arms importer, reflecting huge market leverage to extract defence offset benefits. The road to localisation has been through overseas acquisition, with the desire to succeed emerging from a stronger national identity along with a determination to exploit strategically unbounded capability opportunities.
Keywords: Strategic, Defence & Security Studies; 3502 Banking, finance and investment; 3801 Applied economics; Saudi Arabia; vision 2030; defence offset; defence industrial localisation